Mama Kris a reception analysis and identification study of single mothers with Kris Aquino in the Kris list - Mison, Regina Elena de Castro 1996- (2018)
"This thesis is a reception analysis of single mothers with their representations constructed in media that interrogate mothering. Specifically, it determines single mothers' identification with Kris Aquino through selected media texts. This study uses Richard Dyer's and Graeme Turner's discussion of the stars to look into the connection of public and private images and to investigate how Kris Aquino celebrities the single mother. The study also uses Stuart Hall's Reception Theory to understand the receptions single mothers have of Kris in the selected media texts. Furthermore, the study uses Albert Bandura's Social Learning Theory as framework for the identification of single mothers with Kris; if and how it is possible. In this study, I analyze the single mother. Six episodes of The Kris List, including an Extras episode, are individually viewed by single mothers whom I have selected through purposive, convenience, and referral sampling. The receptions of the participants will the be juxtaposed with their oral life histories relevant to my research, specifically regarding their being a single mother. I believe grasping the meaning-making structures of each participant is essential in determining identification. Among five single mothers, only four were able to identify with Kris. Their respective lived stories and own interpretation of the word 'identification' played crucial factors for identification to actualize. Furthermore, it did not matter if they were fans of the star of nor. Identification occurred by means of similarity, affinity and empathy. Through learning if and how identification with Kris is possible, I hope to show the power of negotiation that audiences have over the meanings brought about by media figures, to inform misguided assumptions about single mothers, and to contribute to the local discourse on the said group of women."